The Influence of Accounting Student Perceptions About Taxes, Tax Brevet and Motivation on Career Interest in Taxation - Wahyu Al Akbar; Herman Ernandi (Indonesian Journal of Law and Economics Review, 2022)
The purpose of this study was to examine and obtain evidence regarding (1) accounting students' perceptions of taxation on interest in a career in taxation, (2) tax brevet on interest in a career in taxation, (3) motivation for interest in a career in taxation. This research is a type of quantitative research with hypothesis testing. The sample used in this study was 85 accounting students at Muhammadiyah Sidoarjo University consisting of semesters 6, 8 and 10. The analytical tools used were multiple linear regression test, correlation coefficient (R), coefficient of determination (R²), t test, and test. F using the SPSS version 18.0 for windows program. This primary data was obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The results of the validity and reliability test showed that the data were valid and reliable. The results of the t-test indicate that the student's perception of taxes, tax brevet, and motivation partially affect the interest in a career in taxation.